Gestão gerencialista e trabalho docente: aproximações com a produção de subjetividades na contemporaneidade - Santos, Renata Gabriele dos (2020)
The Managerial Management, or managerialism, is known for facilitating management practices that enable the exercise of power through factors linked to rationality. This ideological form of management encourages the search for results and contributes to the development of a society that manages everything. Once the reproduction of managerial practices, they can go beyond the organizational scope and reach different spheres of the social order, the conceptions about work, in themselves, also come to be directly influenced by this ideology. In this way, the present study aims to analyze the production of subjectivities built from the managerialism in the daily work of teaching in private Higher Education Institutions (HEI). This research is characterized as qualitative and exploratory-descriptive study. For data collection was used as a participant observation and semi-structured interviews. Were interviewed 16 professors from 3 private HEIs in the city of Curitiba-PR. The analyzes were organized into four categories (Teaching Work – The research subjects, their choices and perceptions, having as subcategories characteristics of qualification, degree and expectations; Teaching work in its senses; Organization of teaching work – Contemporary dilemmas and finally managerialism and its consequences for teachers). The results revealed that the influence of managerialism on the work of professor in private HEIs is not presented in an isolated way, on the contrary, it is articulated in its objective (intensification and fragmentation of teaching practice) and subjective (combined with fascination and seduction at a psychological level ). Finally, each professor builds a singular trajectory in the process of development and formation of their professional profile, producing their subjectivities from the understanding of two poles, singularization or individuation, that lead them to reproduce managerialist norms or to establish lines of escape capable of breaking with their subjection.